Health related quality of life among postmenopausal women of Siddharthanagar municipality - Rubina Shrestha; Saneep Shrestha; Chet Kant Bhusal; Pradip Chhetri (Journal of Universal College of Medical Sciences, 2026)
INTRODUCTION Menopause is the permanent cessation of menstruation caused by the loss of ovarian follicular activity and subsequent hormonal deficiency. It significantly affects woman’s quality of life because of the accompanying physiological, psychological, and social changes. The present study aimed to assess the health-related quality of life (HRQoL) and its associated factors among postmenopausal women. MATERIAL AND METHODS A community based cross-sectional study was conducted among 217 postmenopausal women from Siddharthanagar municipality, Nepal. Health-related quality of life was assessed using Menopausal Rating Scale (MRS). Logistic regression analysis was performed, adjusted odds ratios (AOR) with a 95% confidence interval (CI) was calculated to identify factors associated with HRQoL. A p-value of less than 0.05 was considered statistically significant. RESULTS Overall, 72.35% of postmenopausal women had poor quality of life. The mean and the standard deviation of the total MRS score was 13.32±7.41. Significantly associated factors included education (AOR= 0.38, 95%CI: 0.16-0.90), occupation (AOR= 2.63, 95% CI: 1.34-5.15), age at menopause (AOR= 0.38, 95%CI: 0.20-0.74) and duration of menopause in years (AOR= 2.26, 95%CI: 1.18- 4.35). CONCLUSION Findings of the study highlight the need for targeted health interventions and awareness programs aimed at improving the overall quality of life among postmenopausal women.